POVERTY REDUCTION BEST PRACTICES IN BANYUWANGI REGENCY - Emi Hidayati; Fitriatul Masruroh (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The poverty reduction policy, which was marked by the issuance of various regulations, was responded by the Banyuwangi Regency Government through 6 regional regulations, 8 regent regulations, 29 regent decrees and 1 Regent circular. As well as various breakthrough programs spread across 14 OPDs (Regional Apparatus Organizations). The purpose of this study describes the variety of services as the government's commitment in the form of innovative poverty reduction policies and strategies through collaboration across Regional Apparatus Organizations and multistakeholders as stated in the Banyuwangi Regency Poverty Reduction Plan document 2021 – 2026. Data collection is carried out with in-depth interviews and documentation to obtain data. The collected data is then analyzed by discussing the theory of policy innovation and presented using a qualitative descriptive approach. The results of this study show that through the forms of innovative poverty reduction programs in Banyuwangi Regency, it can reduce the poverty rate from 20% in 2009 to 7.08% in 2021, the highest achievement in East Java.